Análise comparativa de tempo de execução entre os modelos construtivos light steel frame e alvenaria convencional para a construção de habitações sociais - Santini, Caetano Cesar Santos (2023)
In order to keep up with rapid population growth, the construction sector has been dedicated to exploring more effective construction materials and systems to accelerate productivity and reduce losses, meeting housing demand. One of the alternatives found is the Light Steel Frame system, which proves to be one of the options capable of addressing all these needs. However, in Brazil, the conventional masonry model is the most widely used system in construction, despite its low productivity and high waste of material. Therefore, through a literature review, this study aims to present the construction stages of the Light Steel Frame model and conduct a comparative analysis, regarding the execution time, with the conventional masonry model, as an alternative for the construction of social housing. Thus, this study seeks to demonstrate that Light Steel Frame offers a sustainable, clean, and dry construction, as it is an industrialized system formed by standardized steel profiles, and in terms of execution time, it can be observed that the Light Steel Frame model proves to be a more efficient system for the construction of social housing.